Students' Strategies of Measuring Time Using Traditional Gasing Game in Third Grade of Primary School - Jaelani, Anton; Hartono, Yusuf; Putri, Ratu Ilma Indra (Journal on Mathematics Education, 2013)
Understanding of measuring time has difficulty for children because it is intangible. Standar units often use directly by teacher for learning time measurement. Many researches involved game in designing learning material to facilitate fun and meaningful learning for children. For this reason, learning of time measurement that connect with children's daily experience was designed. The context of this research was traditional gasing game. The study is situated in implementation of Indonesian version of Realistic Mathematics Education, labeled as PMRI. This research aimed acquire learning trajectory of time measurement using traditional gasing game for the third grader of primary school by describing students' progress in learning. Design research methodology comprising preparing for the experiment, teaching experiment, and retrospective analysis was used. The research was conducted in SD (Sekolah Dasar) Pusri (Pupuk Sriwijaya) Palembang as one of PMRI (Pendidikan Matematika Realistik Indonesia) school. The result of the teaching experiment showed that learning design could foster students to experience reinvention of time measurement historically. It stimulated students to emerge their sense of time, measure time using non standar unit, understand the concept of standard unit, and measure time using standar unit. Students' strategies that were emerged showed students' progress through situation and problems that were provided by traditional gasing game.